Impact of globalization and regional integration within MERCOSUR on the transformation of the Brazilian automobile industry in the years 1990–2006 - Wójtowicz, Mirosław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
The aim of this paper is determining the influence of the globalization and regional integration processes on the Brazilian automobile industry. The paper also contains the analysis of changes in the state’s industrial policy towards this sector and their influence on winning new foreign investments. The analysis also concerns changes in the MERCOSUR integration policy towards the automobile industry. It was observed that the changes that occurred in the Brazilian automobile industry in the years 1990-2006 are to a large extent a consequence of world-wide transformations in the sector, caused by globalization. On one hand, the changes consisted in modernizing the existing plants, and on the other hand - in emergence of completely new enterprises that aimed at global expansion on the so-called rising markets. This led to the increase in production, diversification of the assortment of available models, and the increase in competition on the Brazilian market.As for integration policy, the member states tried to postpone as long as possible complete liberalization of products trade in this industry within MERCOSUR. Owing to this, they were able to conduct individual policies in this sector, on one hand trying to maintain the barriers that protected their domestic markets, and on the other hand, trying to offer as much as possible to attract foreign investors. This led to numerous conflicts and great tension, chiefly between Argentina and Brazil, which endangered the process of economic integration. Still, the emerging problems were successfully overcome and the barriers for automobile industry trade within MERCOSUR were gradually eliminated. It was reflected in the rapid increase in car trade between the two countries in years 2003-2006.